Star Formation Density and Galactic Outflows at Z~2 - (:unkn) unknown (My University, 2017)
Galactic-scale outflows of gas play a significant role in galaxy evolution. They push gas to larger radii, slowing the star formation rate near the center of the galaxy, and increasing it at larger radii. Eventually, these outflows can expel the gas from the galaxy, depositing metals into the intergalactic medium, and limiting star formation in the galaxy. Galaxies from the Keck Baryonic Structure Survey (KBSS) and 3D- Hubble Space Telescope (3D-HST) Survey were used in order to measure the velocities of galactic outflows from the KBSS spectra, and the grism spectra from the 3D- HST survey were used in order to map the sizes of star forming regions based on emission lines. These galaxies were filtered such that only galaxies with prominent [OIII] λλ4959, 5007 doublet emissions and whose outflow velocities could be calculated were kept. After the filter, 52 galaxies remained. Local galaxies with high surface densities of star formation are known to have stronger galactic outflows. To test if this is true at z∼2, the [OIII] luminosity surface density was used as an analog to the SFR, and it was compared to the outflow velocity in each galaxy. A correlation significance of 0.4σ was found, indicating no correlation between the two values. This disagrees with some existing results. The lack of correlation could be due to a lack of range in galaxy properties. It is recommended to use Hα emission to more directly measure the star formation rates in the future, instead of using [OIII] as an analog to the SFR.